Sales management - Mathur, U. C. (New Age International (P) Ltd., Publishers, 2008)
Sales Management is arguably the most important of all the marketing functions, as only through sales companies earn money. Considering its primacy in today`s competitive business scenario, companies keep looking for ideal sales persons, ``the illusive individual.`` The book is meant to help the students to reach the pinnacle of Sales Management learning.
Keywords: Sales management